Muscular effects of statins in the elderly female: a review - Bhardwaj S (Dove Medical Press, 2013)
Shilpa Bhardwaj,1,2 Shalini Selvarajah,3 Eric B Schneider31Griffin Hospital, Derby, CT, USA; 2Yale University, New Haven, CT, USA; 3Center for Surgical Trials and Outcomes Research, Johns Hopkins School of Medicine, Baltimore, MD, USAAbstract: Statins have demonstrated substantial benefits in supporting cardiovascular health. Older individuals are more likely to experience the well-known muscle-related side effects of statins compared with younger individuals. Elderly females may be especially vulnerable to statin-related muscle disorder. This review will collate and discuss statin-related muscular effects, examine their molecular and genetic basis, and how these apply specifically to elderly women. Developing strategies to reduce the incidence of statin-induced myopathy in older adult women could contribute to a significant reduction in the overall incidence of statin-induced muscle disorder in this vulnerable group of patients. Reducing statin-related muscle disorder would likely improve overall patient compliance, thereby leading to an increase in improved short- and long-term outcomes associated with appropriate use of statins.Keywords: statins, older adults, elderly, females, epidemiology